Asuhan Keperawatan Keluarga Pada Keluarga Dengan Gastritis Di Wilayah Kerja Puskesmas Sungai Lasi Kecematan Ix Koto Sungai Lasi Kabupaten Solok 2026 - Indah Julia; Armaita Armaita; Sandra Dewi; Hasmita Hasmita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
According to World Health Organization (WHO), the incidence of gastritis in the world reached 1.8 million to 2.1 million people. The number of cases in Indonesia is quite high, which is around 274,396 cases or 40% of the population of 238,452,952. Based on data in Sumatra province, gastritis sufferers are 17,354 (5.62%) of 308,756 people. In Solok district, the number of cases is 12,108 who suffer from gastritis. At the Sungai Lasi Community Health Center, the ranking is 3rd, namely 364 people suffering from gastritis. The purpose of this study is to understand and apply family nursing care to patients with gastritis. This study uses a case study research method. This case study was conducted at Sungai Lasi Community Health Center on February 23 to February 28, 2026. After the assessment, patient Mr. M was diagnosed with acute pain related to physiological injury agents, knowledge deficit related to lack of exposure to information, ineffective health management, and ineffectiveness of Family Health Care Patterns. The interventions provided included pain management, deep breathing relaxation techniques, traditional medicine education, how to make it, and health education. Evaluations were obtained from the implementation provided. Based on the case study conducted, it can be concluded that the implementation of family nursing care that has been carried out for 5 days has resulted in 3 well-controlled nursing problems. The results of this study are expected to be a reference for authors, educational institutions, families, and health workers in improving the understanding and quality of family nursing care in patients with gastritis.